Analisis Kesulitan Mahasiswa dalam Memahami Konsep Tasybīh serta Strategi Pembelajarannya: Studi pada Mahasiswa PBA STAI Nurul Iman Parung, Bogor - Parhan, Parhan; Isyanto, Nur; Muadib, Ihwanul (STAINI Press, 2026)
The study of balāghah, particularly the subject of tasybīh, plays an important role in developing advanced Arabic text analysis skills. However, sixth-semester PBA students at STAI Nurul Iman Parung, Bogor, still face various difficulties in understanding the concept of tasybīh, both in terms of its elements and its application in the Qur'an and Arabic literature. This condition has an impact on the students' limited ability to grasp the implicit meaning and rhetorical dimensions of the Arabic language. This study aims to describe the difficulties experienced by students in understanding tasybīh, analyse the contributing factors, and formulate appropriate learning strategies to improve their stylistic analysis skills. The research focuses on the relationship between conceptual mastery, linguistic ability, and pedagogical approaches applied in balāghah lectures. The study used a descriptive qualitative approach with 32 male sixth-semester PBA students as subjects. Data were collected through in-depth interviews, open and closed questionnaires, and learning document studies. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, and verified through triangulation of techniques and sources. The results showed that students experienced difficulties in understanding the elements of tasybīh, classifying its types, and analysing its functions in texts. These difficulties were influenced by limited vocabulary, the complexity of Arabic sentence structure, and a learning approach that was still oriented towards memorising theory. This study recommends text-based learning, a task-based approach, and the gradual application of conceptual scaffolding so that students are able to understand tasybīh in an applied manner. These findings are expected to strengthen the development of balāghah pedagogy in Arabic Language Education in higher education.